Remaining useful life prediction for degrading systems with random shocks considering measurement uncertainty. (October 2021) - Kong, Xuefeng; Yang, Jun; Li, Lei
Highlights: An RUL prediction framework with shocks and measurement uncertainty is proposed. Both harmful shocks and beneficial shocks are considered in the proposed method. A state-space model is used to depict the transition process of the system state. Model parameters are estimated by an efficient method based on EM-PF algorithm. Numerical study and real case studies show the superiority of the proposed method. Abstract: Degradation data have been widely used for the remaining useful life (RUL) prediction of systems. Most existing works apply a preset model to capture the degradation process and focus on the degradation process without shocks or constant shock effects. More generally, the actual degradation path is unobservable due to the existence of measurement uncertainty, which interferes with the determination of the degradation model. Besides, the effect of random shocks is usually fluctuating. Given these problems, a general degradation model with the random shock fluctuant effects considering the measurement uncertainty is first developed to describe the degradation process, and a two-step approach combining the arithmetic average filter and the Bayesian information criterion is adopted to identify the degradation path. Subsequently, the transfer processes of the actual degradation state and the abrupt change caused by shocks are depicted using a two-dimensional state-space model, and an expectation-maximization algorithm combined with the particle filtering is developed for parameter estimation. Furthermore, the explicit solution of RUL distribution is obtained when only considering harmful shocks, while a simulation method of RUL distribution is provided when both harmful and beneficial shocks exist. Finally, the effectiveness of the proposed method is verified by a numerical example and two practical case studies.